DENSINY OF MICROBIAL COLONIZATION OF YOUNG PEOPLE ORAL CAVITY DEPENDING ON THE CARIES INTENSITY - Petrushanko, T.A.; Chereda, V.V.; Loban', G.A. (World of Medicine and Biology, 2013)
Individuals with caries have logarithmic microbial count of aerobic and anaerobic bacteria higher then people with intact teeth. We found average power correlation connection between hygienic indices and the level of intensity of caries process, between logarithmic microbial count of aerobic and anaerobic bacteria, hygienic indices and intensity of caries.